The Farahzad Neighbourhood of Tehran: Land Use Transition in the City Periphery - Seyedeh Zahra Hosseini; Martin Wynn; Seyed Mostafa Parpanchi (Urban Science, 2025)
Since the 1960s, Iran’s major cities have experienced significant migration from the country’s rural areas and from other nations. Although many urban planning and design concepts can be traced back to Iran, the country’s planning machinery has failed to effectively regulate urban growth, notably in the city peripheries, where land use has changed radically as semi-rural areas have been developed in a haphazard fashion with scant adherence to existing plans and planning regulations. Farahzad is one such area in the urban periphery of Tehran, where a range of sub-standard dwellings have been built, and urban services are deficient in many regards. This article examines how the urban landscape has evolved, how the resident population has grown, and the nature of the social and economic issues that persist today. The research method combines an analysis of the extant literature and local authority documentation, images developed from GIS data, and first-hand interviews with local practitioners to explore the growth of the neighbourhood in recent decades and assess the current problems confronting both residents and local authorities. The novelty of this article lies in the use of GIS-generated images and urban fabric classifications to assess the growth of the neighbourhood since the turn of century, during which time the planning machinery has generally failed to provide an adequate framework for development in this area of the Tehran urban periphery. Indeed, findings suggest that land use zoning has played little part in guiding or controlling urban development in Farahzad, and that identifying urban fabrics may prove a useful way of assessing socio-economic and physical development needs in such circumstances. This article makes a small contribution to our understanding of the change dynamics in a peripheral neighbourhood of a major city in the developing world.